Assessing the causality between pulmonary arterial hypertension and cancer: insights from Mendelian randomization - Yang Fu; Xinwang Duan; Wei Zhou (Discover Oncology)
Abstract Background Previous clinical studies have suggested an increased risk of tumor development in patients with pulmonary arterial hypertension (PAH). However, it remains unclear whether there is a causal relationship between PAH and tumor occurrence. This study investigates the causal link between PAH and cancer from a genetic perspective using Mendelian randomization (MR). Method Genome-wide association study (GWAS) summary data for PAH and various common cancer types were obtained from the GWAS Catalog. Single nucleotide polymorphisms (SNPs) significantly associated with PAH at the genome-wide significance threshold (P < 1 × 10−6) were selected as instrumental variables (IVs). Inverse-variance weighted (IVW) was used as the primary method for MR analysis, with sensitivity analyses including tests for heterogeneity and horizontal pleiotropy. Results The results from the IVW analysis indicate that genetically proxied PAH is associated with an increased risk of liver cancer [odd ratio (OR) 1.11, 95% confidence interval (CI) 1.01–1.22, P = 0.025), while showing no significant causal relationship with other common types of tumors (thyroid cancer: OR 0.95, 95% CI 0.86–1.06, P = 0.360; lung cancer: OR 0.95, 95% CI 0.90–1.01, P = 0.129; gastric cancer: OR 0.97, 95% CI 0.93–1.02, P = 0.243; colorectal cancer: OR 1.01, 95% CI 0.98–1.05, P = 0.412). Except for the MR analysis examining the causal effect of PAH on lung cancer (P = 0.049), the remaining MR analyses displayed no significant heterogeneity (P > 0.05). Additionally, the MR-Egger intercept test did not find evidence of horizontal pleiotropy (P > 0.05). Conclusion This study highlights that PAH may serve as a potential risk factor for this liver cancer. Future research should aim to elucidate the biological mechanisms at play and explore the potential for early interventions that could mitigate cancer risk in this vulnerable population.